2012
DOI: 10.1016/j.neuroimage.2011.09.057
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of myelination by phase imaging at high magnetic field

Abstract: The present study evaluated the potential of using the phase of T 2 * weighted MR images to characterize myelination during brain development and pathology in rodents at 9.4 T. Phase contrast correlated with myelin content assessed by histology and suggests that most contrast between white and cortical gray matter is modulated by myelin. Ex vivo experiments showed that gray-white matter phase contrast remains unchanged after iron extraction. In dysmyelinated shiverer mice, phase imaging correlated strongly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
93
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 46 publications
5
93
0
Order By: Relevance
“…Myelin content does contribute to the gray and white matter contrast in phase imaging (C. Liu et al, 2011;Lodygensky et al, 2012) yet, not only is the myelin susceptibility anisotropic, its contribution to the measured phase images is driven by the microstructural compartmentalization of lipid organization and its orientation in respect to the static magnetic field (He and Yablonskiy, 2009;Luo et al, 2014;Wharton and Bowtell, 2013;Yablonskiy et al, 2012). These mechanisms are not taken into account in the COSMOS formalism, but they should only be dominating factors in regions where tissue is highly anisotropic (unlike grey matter).…”
Section: Introductionmentioning
confidence: 99%
“…Myelin content does contribute to the gray and white matter contrast in phase imaging (C. Liu et al, 2011;Lodygensky et al, 2012) yet, not only is the myelin susceptibility anisotropic, its contribution to the measured phase images is driven by the microstructural compartmentalization of lipid organization and its orientation in respect to the static magnetic field (He and Yablonskiy, 2009;Luo et al, 2014;Wharton and Bowtell, 2013;Yablonskiy et al, 2012). These mechanisms are not taken into account in the COSMOS formalism, but they should only be dominating factors in regions where tissue is highly anisotropic (unlike grey matter).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that the source of the anisotropic susceptibility of WM is the myelin sheath (19,(30)(31)(32). This is composed of multiple lipid bilayers in which the lipid chains are radially oriented with respect to the approximately cylindrical sheath.…”
Section: Introductionmentioning
confidence: 99%
“…The other proposed contributor to the phase contrast, particularly between white and gray matter, is myelin where pathological demyelination has shown a decreased phase contrast between gray and white matter (C. Liu et al, 2011;Lodygensky et al, 2012) and good correlation was found between myelination and phase contrast during development. (Lodygensky et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Iron contributes to tissue contrast especially in the deep gray matter (globus pallidus, putamen and caudate) which has histologically derived high iron concentration showing good correlation with phase and susceptibility contrast (Bilgic et al, 2012;Schweser et al, 2011;Wharton and Bowtell, 2010). The other proposed contributor to the phase contrast, particularly between white and gray matter, is myelin where pathological demyelination has shown a decreased phase contrast between gray and white matter (C. Liu et al, 2011;Lodygensky et al, 2012) and good correlation was found between myelination and phase contrast during development. (Lodygensky et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation